Responses to risks and opportunities associated with pollinators and pollination - Dicks, Lynn (2016)
The overall aim of the thematic assessment of Pollinators, Pollination and Food Production is to assess animal pollination as a regulating ecosystem service under pinning food production in the context of its contribution to nature'sgifts to people and supporting a good quality of life. Toachieve this, the focus is on the role of native and exoticpollinators, the status of, and trends in pollinators andpollinator-plant networks and pollination, drivers of change,impacts on human well-being, food production in responseto pollination declines and deficits and the effectiveness ofresponses from various governance systems to pollinationdeclines and deficits. The scope is global, covering allcontinents except Antarctica, where no pollinators areknown. The assessment brings together contributions notonly from natural, social and economic science perspectives but also from knowledge of indigenous and local community stake holders and practitioners.The assessment strives to critically review the broadest range of evidence and make its findings readily availableto support policy and management responses to declinesand deficits in pollination. The report represents the firstIPBES thematic assessment deliverable that aims toidentify policy-relevant findings for decision-making ingovernment, the private sector and civil society, as wellas helping to demonstrate how an essential ecosystem service could potentially contribute to the post-2015 development agenda